The Relationship Between Self-Concept and Academic Achievement of 5th Semester Students at Stikes Hamzar East Lombok - ikhwani, dina alfiana; Farlina, Baiq Fina; Aupia, Anatun; Irwansyah, Irwansyah (INDOGENIUS, 2025)
Background & Objective: Student academic achievement is one of the things that characterizes the quality of students. Academic achievement is a change in behavioral skills or abilities that can increase over time that is not caused by the growth process, but through learning situations. Relationship between self-concept and academic achievement of 5th semester students of STIKes Hamzar East Lombok. Method: The type of research used is quantitative research with a cross sectional approach. The sampling technique in this study used total sampling with a total sample size of 56 samples. Result: This study shows that most (58.9%) students' self-concept in the Moderate category as many as 33 people, students' academic achievement shows that most (83.9%) are categorized as very satisfying as many as 47 people. This study shows the results of statistical tests using Spearman rank on the Self-Concept variable with academic achievement with a p-value of 0.01 <0.05, which means that there is a significant relationship between student self-concept and academic achievement. Conclusion: This study can be concluded that there is a relationship between student self-concept and academic achievement at STIKes Hamzar East Lombok.